2020
DOI: 10.1128/aac.00479-20
|View full text |Cite
|
Sign up to set email alerts
|

A Multimethod, Multicountry Evaluation of Breakpoints for Bedaquiline Resistance Determination

Abstract: Criteria defining bedaquiline resistance for tuberculosis have been proposed addressing an emerging concern. We evaluated bedaquiline phenotypic drug susceptibility testing (pDST) criteria using drug-resistant tuberculosis clinical isolates tested at five reference laboratories. Isolates were tested at the proposed bedaquiline MGIT960 and 7H11 Agar Proportion (AP) critical concentrations, and dilutions higher. The epidemiological cut-off value for the broth microdilution (BMD) plates (frozen and dry) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, in the longitudinal cohort, primary transmission was 6•7%, which is similar to the 7•9% observed in the cross-sectional analysis. The occurrence of bedaquiline resistance at baseline at a prevalence of 2-4% in multiple regions among patients without previous exposure, 21 which is not sufficiently explained directly by the factors we identified, suggests a generalised occurrence.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, in the longitudinal cohort, primary transmission was 6•7%, which is similar to the 7•9% observed in the cross-sectional analysis. The occurrence of bedaquiline resistance at baseline at a prevalence of 2-4% in multiple regions among patients without previous exposure, 21 which is not sufficiently explained directly by the factors we identified, suggests a generalised occurrence.…”
Section: Discussionmentioning
confidence: 66%
“…Over the surveillance period (2015-19) and under programmatic conditions, 3•8% of patients had baseline isolates resistant to bedaquiline, correlating with data from clinical trials done in South Africa (16 [4%] of 391). 11 A multicountry surveillance study using isolates from patients without exposure to bedaquiline across 28 countries showed a prevalence of 2•2% (95% CI 1•1-3•9), 21 and an identical point prevalence was observed in a multicentre study from China. 22 Bedaquiline resistance was associated with Rv0678 mutations across all studies, including our study.…”
Section: Discussionmentioning
confidence: 88%
“…This value was supported by two subsequent studies, the first of which showed that that the sensitivity and specificity is maximised with a ECOFF/ECV of 0.12 mg/L compared to 0.25 mg/L (43). The second confirmed this value, however also stated that the 99 th percentile of the wild-type population was 0.25 mg/L (44). This illustrates that the exact value can be difficult to pin down when different ECOFF/ECV definitions are used;…”
Section: Discussionmentioning
confidence: 69%
“…This value was supported by two subsequent studies, the first of which showed that that the sensitivity and specificity is maximised with a ECOFF/ECV of 0.12 mg/L compared to 0.25 mg/L (39). The second confirmed this value, however also stated that the 99 th percentile of the wild-type population was 0.25 mg/L (40). This illustrates that the exact value can be difficult to pin down when different ECOFF/ECV definitions are used; hopefully the number and diversity of samples in our study will help resolve this important question.…”
Section: Discussionmentioning
confidence: 69%